Padi4 In Predicting The Severity And Recovery Of Early Stroke (Texas Journal of Medical Science, 2025)
A comparison of the results of the study with data on the role of PADI4 in transport and immunomodulation shows that this protein is important for cell regeneration and the prevention of irreversible consequences through the catalysis of posttranslational modifications. The level of PADI4 below 80.1 u/ml is associated with an increased risk of mortality, while its excess improves the chances of survival and correlates with favorable functional outcomes. Thus, measuring the level of PADI4 on the first day after an ischemic stroke can serve as an indicator of prognosis and a basis for correcting metabolic therapy